The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1002/(sici)1096-8628(20000424)91:5<377::aid-ajmg11>3.0.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Y chromatin directly in gonadal tissue by fluorescence in situ hybridization (FISH): Significance for Ullrich-Turner syndrome screening in the cytogenetics laboratory

Abstract: The presence of Y chromatin in individuals with Ullrich-Turner syndrome (UTS) confers a risk for gonadoblastoma. In mosaic cases, little is known about Y chromatin distribution in gonads. Fluorescence in situ hybridization (FISH) is a direct approach to assess the extent of Y chromatin mosaicism in gonads. Gonadal tissue from four patients with mosaic karyotypes were analyzed by routine cytogenetics and FISH with X and Y centromere probes. Y chromatin was present in gonads in varying percentages in these patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
1

Year Published

2001
2001
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 21 publications
1
16
1
Order By: Relevance
“…As in previous studies 7,8,10 we observed no correlation between the degree of mosaicism in PBL and in gonadal cells, nor was the PBL karyotype able to predict the differentiation patterns that had developed in the dysgenetic gonad. Differential growth of the 45,X and 46,XY cell lines in vitro and the selection of a subset of clones for PBL karyotyping cannot be excluded.…”
Section: Discussioncontrasting
confidence: 52%
See 3 more Smart Citations
“…As in previous studies 7,8,10 we observed no correlation between the degree of mosaicism in PBL and in gonadal cells, nor was the PBL karyotype able to predict the differentiation patterns that had developed in the dysgenetic gonad. Differential growth of the 45,X and 46,XY cell lines in vitro and the selection of a subset of clones for PBL karyotyping cannot be excluded.…”
Section: Discussioncontrasting
confidence: 52%
“…In spite of our increasing knowledge on genes involved in normal sex development, the disturbed gonadal differentiation processes that underlie gonadal dysgenesis (GD) syndromes are less well understood 1–5 . Little is known about the correlations between peripheral blood (PBL) karyotype and/or skin fibroblasts on the one hand, and the gonadal karyotype and morphological differentiation patterns of the gonad on the other 6–11 . Traditionally, in GD, three differentiation patterns have been described: (dysgenetic) testicular tissue, ovarian tissue, and streak gonads.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, monozygotic twins with different phenotypes (presumably due to different ratios of mosaicism of gonadal tissue) have been reported (20,21,22). Different levels of mosaicism of karyotype between lymphocytes and gonadal tissues have already been reported (23,24,25). The results of all four cases in this study confirmed that karyotype analysis of the gonad is more consistent with the phenotype of the gonad and external genitalia.…”
Section: Discussionmentioning
confidence: 98%